Psychosocial outcomes of COVID-19 pandemic on healthcare workers in maternity services - Recep Erin; Yeşim Bayoğlu Tekin (Taylor & Francis Group, 2022)
Aim We investigated the effects of the COVID-19 outbreak on social support and anxiety levels in healthcare professionals working in maternity services situated in Trabzon, Turkey. Materials and Methods Our study was designed retrospectively and observationally. Social support to the participants was measured using a scale called the multidimensional scale of perceived social support (MSPSS). State anxiety scale (STAI TX-1) and trait anxiety scale (STAI TX-2) were used to determine the level of anxiety. All scales were measured before and during the pandemic. Independent t-test and one-way ANOVA were used to analyze the data where p < 0.05 was considered significant. Results The participants' demographic data (n = 96) included the mean age of doctors (n = 30), midwives (n = 34), and nurses (n = 32) which were 41.38 ± 4.16/38.58 ± 1.79/37.34 ± 2.19, respectively. Mean gravida was 1.69 ± 2.87/2.23 ± 0.12/2.31 ± 0.14, respectively. Mean BMI was 24.69 ± 2.87/26.04 ± 0.8/25.69 ± 1.98 in the same order (p > 0.05). The total mean values of the MSPSS, STAI TX-1, STAI TX-2 scales before and during the pandemic were found as 66.55 ± 6.63 − 55.25 ± 4.76, 36.71 ± 10.04 − 50.08 ± 11.65, 37.33 ± 8.09 − 53.32 ± 9.94, respectively. A significant difference was found for the mean of all scales amongst the groups (p < 0.05). Conclusion During the COVID-19 pandemic, a significant number of healthcare workers were deprived of social support and their anxiety levels increased.